2012
DOI: 10.21273/hortsci.47.5.648
|View full text |Cite
|
Sign up to set email alerts
|

Response of Highbush Blueberry to Nitrogen Fertilizer During Field Establishment, I: Accumulation and Allocation of Fertilizer Nitrogen and Biomass

Abstract: The effects of nitrogen (N) fertilizer application on plant growth, N uptake, and biomass and N allocation in highbush blueberry (Vaccinium corymbosum L. ‘Bluecrop’) were determined during the first 2 years of field establishment. Plants were either grown without N fertilizer after planting (0N) or were fertilized with 50, 100, or 150 kg·ha−1 of N (50N, 100N, 150N, respectively) per year using 15N-depleted ammonium sulfate the first y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
67
5
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(88 citation statements)
references
References 14 publications
15
67
5
1
Order By: Relevance
“…Applications greater than 34 kg N ha (1 likewise did not increase yield any further in young blueberry plants in New Jersey, and rates !64 kg N ha (1 were detrimental to early fruit production (Eck 1977). Similar detrimental effects have been observed on growth of young blueberry plants in western Oregon (Ban˜ados et al 2012). In another western Oregon study, Bryla and Machado (2011) found that granular ammonium sulphate applications maximized growth in young 'Bluecrop' blueberry plants at 50 kg N ha (1 or less and reduced growth at 100Á150 kg N ha (1 .…”
Section: Yieldsupporting
confidence: 59%
See 1 more Smart Citation
“…Applications greater than 34 kg N ha (1 likewise did not increase yield any further in young blueberry plants in New Jersey, and rates !64 kg N ha (1 were detrimental to early fruit production (Eck 1977). Similar detrimental effects have been observed on growth of young blueberry plants in western Oregon (Ban˜ados et al 2012). In another western Oregon study, Bryla and Machado (2011) found that granular ammonium sulphate applications maximized growth in young 'Bluecrop' blueberry plants at 50 kg N ha (1 or less and reduced growth at 100Á150 kg N ha (1 .…”
Section: Yieldsupporting
confidence: 59%
“…Fertigation also enables more precise control over fertilizer composition, which can be easily changed throughout the growing season, depending on plant requirements as determined by foliar analysis. When granular N fertilizer is applied to blueberry, N uptake is fairly constant throughout the growing season in young, uncropped plants, but greater during peaks in vegetative growth in the spring and during fruit development in early summer than after harvest in fruiting plants (Throop and Hanson 1997;Ban˜ados et al 2012). There is no published information available on N uptake by fertigated blueberry plants.…”
mentioning
confidence: 99%
“…Even though leaf N was significantly lower in 2013 than in 2014 at both sites, it was barely below current sufficiency levels only at the organic site (Table 6). Leaf N may have increased at the conventional site as more N fertilizer was applied in 2014 (Table 1), since leaf N is positively correlated with fertilization rate in blueberry (Bañados et al, 2012;Retamales and Hanson, 1990;Spiers, 1983). There was no cultivar effect on leaf N at the organic site, whereas 'Draper' had a higher leaf N than all other cultivars at the conventional site.…”
Section: Resultsmentioning
confidence: 99%
“…Precision management in other woody species has attempted to limit supplementary N applications to the times when remobilization and soil supply cannot meet demand (Neilsen and Neilsen ; Bańados et al ), often in spring after the first leaves have emerged, when soil temperatures limit soil N mineralization. The most efficient method of applying N to the root zone is through the irrigation system (i.e., fertigation) (Bar‐Josef ; Neilsen et al ; Neilsen and Neilsen ; Tagliavini and Marangoni ) at high frequency (Silber et al ).…”
Section: Bmps To Reduce Nitrate Loadingmentioning
confidence: 99%
“…Fall planting of annual cover crops is a recommended practice in BC (BCMA ). Annual cover crops of cereal rye or barley planted in late summer or early fall did not suppress raspberry growth (Freyman ; Zebarth et al ; Bowen and Freyman ) and took up residual nitrate from the soil root zone, preventing it from being leached by autumn and winter rainfall (Zebarth et al ).…”
Section: Bmps To Reduce Nitrate Loadingmentioning
confidence: 99%